Comparative Outcomes of Endourological Procedures in Urolithiasis: A Narrative Literature Review of PCNL, URS, and ESWL - Muhammad Fauzan Farhat (Jurnal Kedokteran Methodist, 2025)
Urolithiasis remains a recurrent and resource-intensive condition, where endourological interventions are selected based on stone burden, location, anatomy, patient preference, stone-free rate, safety, retreatment, recovery, and cost. This narrative review assesses percutaneous nephrolithotomy (PCNL), ureteroscopy or retrograde intrarenal surgery (URS/RIRS), and extracorporeal shock wave lithotripsy (ESWL/SWL). PCNL consistently has the best chance of getting rid of stones, especially for bigger stones, stones in the lower pole, or complicated kidney stone burdens. However, these benefits come with more invasive procedures, longer hospital stays, and more bleeding-related illnesses. ESWL is still the least invasive and often the least expensive option, but the results depend more on the size, density, position, and the gap between the stone and the skin, as well as the need for repeat sessions. Recent evidence suggests that treatment selection should not be limited to a single efficacy hierarchy: PCNL, URS, and ESWL each serve distinct therapeutic functions, and optimal decision-making requires the alignment of procedural benefits with stone- and patient-specific priorities. Keywords: urolithiasis, PCNL, ureteroscopy, retrograde intrarenal surgery, ESWL